2022
DOI: 10.3390/polym14091832
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Synthesis and Characterization of Chitosan-CuO Nanocomposite and Evaluation of Antibacterial Activity against Gram-Positive and -Negative Bacteria

Abstract: Chitosan-copper oxide (CHT-CuO) nanocomposite was synthesized using olive leaf extract (OLE) as reducing agent and CuSO4⋅5H2O as precursor. CHT-CuO nanocomposite was prepared using an in situ method in which OLE was added to a solution of chitosan and CuSO4⋅5H2O mixture in the ratio of 1:5 (v/v) and heated at a temperature of 90 °C. The obtained CHT-CuO nanocomposite was characterized using field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), ultraviolet-visible (UV-Vis) spectrophotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 69 publications
2
11
0
Order By: Relevance
“…The mixture was heated on a magnetic hot plate to a constant temperature of 90 • C for 96 h while being constantly stirred. A gradual change in colour indicated the formation of chitosan-CuO nanocomposite, which was confirmed by UV-vis measurement [32].…”
Section: Preparation and Characterization Of Cht-cuo Nanocompositesmentioning
confidence: 52%
See 1 more Smart Citation
“…The mixture was heated on a magnetic hot plate to a constant temperature of 90 • C for 96 h while being constantly stirred. A gradual change in colour indicated the formation of chitosan-CuO nanocomposite, which was confirmed by UV-vis measurement [32].…”
Section: Preparation and Characterization Of Cht-cuo Nanocompositesmentioning
confidence: 52%
“…Aqueous Olive leaf extract (OLE) was used as the reductant while CuSO 4 •5H 2 O served as the CuO nanoparticles precursor. Details of preparation and characterization of chitosan-CuO nanocomposite are documented in our earlier publication [32]. Briefly, chitosan with masses of 0.5, 1.0, and 2.0 g was weighed into a conical flask (250 mL capacity) and 100 mL distilled water containing 1 mL of acetic acid was added.…”
Section: Preparation and Characterization Of Cht-cuo Nanocompositesmentioning
confidence: 99%
“…Similarly, Rashki et al (2022) reported the absorption peak for the chitosan nanoparticles to be around 300 nm. For the CH-CuO nanoparticles, Umoren et al (2022) characterized the CH-CuO nanocomposites and reported the spectral absorbance peak for the nanocomposite at around 285 nm, while Maheo et al (2022) reported the absorption peak for the green- synthesized CH-CuO nanoparticles at 278 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the nanoparticles of CuO has been combined with polymers or coated on the surface to enable the antibacterial applications. [24,25] Polypyrrole is an organic compound with antibacterial activity due to the strong electrostatic interaction between the positive charges in the polymer structure and the negatively charged bacterial cell wall/membrane. [26][27][28] Positive charges in a form of =NH + can disrupt the bacterial cell wall, interact with the bacterial cell membrane, break the balance of proton transfer, and inhibit cellular respiration, and ultimately lead to cell death.…”
Section: Introducementioning
confidence: 99%
“…Despite of the antimicrobial effect, nanoparticles of copper oxide have shown some deficiencies such as easy to aggregate, insufficient dispersibility and insolubility in water. Therefore, the nanoparticles of CuO has been combined with polymers or coated on the surface to enable the antibacterial applications [24,25] . Polypyrrole is an organic compound with antibacterial activity due to the strong electrostatic interaction between the positive charges in the polymer structure and the negatively charged bacterial cell wall/membrane [26–28] .…”
Section: Introducementioning
confidence: 99%